2007
DOI: 10.2220/biomedres.28.91
|View full text |Cite
|
Sign up to set email alerts
|

An inhaled inducible nitric oxide synthase inhibitor reduces damage of Candida-induced acute lung injury

Abstract: Excessive nitric oxide (NO) generated by inducible nitric oxide synthase (iNOS) aggravates acute lung injury (ALI) by producing peroxynitrite. We previously showed by immunostaining that the expression of iNOS was suppressed by inhalation of N G -nitro-L-arginine methyl ester in mice with Candida-induced ALI. This study tested the hypothesis that a novel iNOS inhibitor suppresses not only iNOS expression, but also iNOS messenger RNA (mRNA) production by interrupting a positive feedback loop at the time of NO p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The temporal association between AhR-mediated elevation in pulmonary neutrophil number and iNOS levels in the infected lung, combined with the reported causal relationship between iNOS and neutrophil recruitment in other model systems (30, 31, 55), suggests a causal relationship may exist. To determine if the AhR-mediated increase in iNOS is necessary for or drives the enhanced neutrophil recruitment to the infected lung, we used the NOS inhibitor N5-[imino(methylamino)methyl]-L-ornithine (L-NMMA).…”
Section: Resultsmentioning
confidence: 89%
“…The temporal association between AhR-mediated elevation in pulmonary neutrophil number and iNOS levels in the infected lung, combined with the reported causal relationship between iNOS and neutrophil recruitment in other model systems (30, 31, 55), suggests a causal relationship may exist. To determine if the AhR-mediated increase in iNOS is necessary for or drives the enhanced neutrophil recruitment to the infected lung, we used the NOS inhibitor N5-[imino(methylamino)methyl]-L-ornithine (L-NMMA).…”
Section: Resultsmentioning
confidence: 89%
“…Ohsugi et al [43] demonstrated that inhaled ONO-1714, a very potent but moderately selective iNOS inhibitor, diminished pulmonary inflammation, NO x and peroxynitrite production and prolonged survival in a Candida albicansinduced ALI model in mice.…”
Section: Ali and Ards (Acute Respiratory Distress Syndrome)mentioning
confidence: 99%
“…We also reported that nitric oxide (NO) produced by inducible nitric oxide synthase (iNOS) played a crucial role in Candida-induced ALI and demonstrated that the iNOS inhibitor L-NAME had a beneficial effect on Candida-induced ALI (17). Furthermore, we showed that a novel iNOS inhibitor, ONO-1714, a novel selective iNOS inhibitor (1S,5S,6R,7R)-7-chloro-3-imino-5-methyl-2-azabicyclo[4.1.0]heptane hydrochloride), reduced Candida-induced ALI (20). Numerous clinical and case studies have indicated that inhaled NO decreases pulmonary hypertension and improves hypoxemia in ARDS (24).…”
Section: Bronchoalveolar Lavage (Bal)mentioning
confidence: 72%